1998
DOI: 10.1002/hep.510270207
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory evoked potentials in subclinical portosystemic encephalopathy: A comparison with psychometric tests

Abstract: We prospectively studied the role of somatosensory evoked potentials (SEPs) and psychometric tests in the assessment of subclinical portosystemic encephalopathy (PSE) Evoked potentials are noninvasive, objective electrical manifestations of the nervous system function in response to stimulation. 3,4 Somatosensory evoked potentials (SEPs) can detect the integrity of somatosensory pathways from the peripheral to the central nervous system. 3,4 SEPs are useful in the objective assessment and monitoring of HE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
(47 reference statements)
3
27
0
2
Order By: Relevance
“…[53][54][55][56][57] Somatosensory evoked potentials (SSEPs) SSEPs explore both nervous transmission from the medulla oblongata to the cortex (central conduction timei.e., the interpeak latency N13-N20-) and hemispheric transmission (middle components of the EP), therefore produce data related to the ones provided by BAEPs and fVEPs, respectively. A minor prolongation of central conduction time in cirrhosis, 37,58 and therefore an alteration in brainstem nervous transmission possibly due to myelopathy or edema was confirmed by SSEPs. However, the prolongation of the middle cortical components (after P25) was found to be much more evident and related with the impairment in neuropsychiatric status 37 and with the risk to develop overt HE in the follow up.…”
Section: Brainstem Auditory Evoked Potentials (Baeps)mentioning
confidence: 76%
See 2 more Smart Citations
“…[53][54][55][56][57] Somatosensory evoked potentials (SSEPs) SSEPs explore both nervous transmission from the medulla oblongata to the cortex (central conduction timei.e., the interpeak latency N13-N20-) and hemispheric transmission (middle components of the EP), therefore produce data related to the ones provided by BAEPs and fVEPs, respectively. A minor prolongation of central conduction time in cirrhosis, 37,58 and therefore an alteration in brainstem nervous transmission possibly due to myelopathy or edema was confirmed by SSEPs. However, the prolongation of the middle cortical components (after P25) was found to be much more evident and related with the impairment in neuropsychiatric status 37 and with the risk to develop overt HE in the follow up.…”
Section: Brainstem Auditory Evoked Potentials (Baeps)mentioning
confidence: 76%
“…A minor prolongation of central conduction time in cirrhosis, 37,58 and therefore an alteration in brainstem nervous transmission possibly due to myelopathy or edema was confirmed by SSEPs. However, the prolongation of the middle cortical components (after P25) was found to be much more evident and related with the impairment in neuropsychiatric status 37 and with the risk to develop overt HE in the follow up. 59 These findings prove that HE influences hemispheric multisynaptic pathways more than subcortical brainstem neurotransmission.…”
Section: Brainstem Auditory Evoked Potentials (Baeps)mentioning
confidence: 76%
See 1 more Smart Citation
“…The SEP recordings were carried out in a quiet and dimly lit room with the subjects in a supine position using a Dantec Counterpoint ( Dantec Elektronik Medicinsk, Skovlunde, Denmark) by a method as described in previous studies [6,13] . Median nerve evoked cortical responses were recorded for N20-N65 inter-peak latencies ( IPLs ).…”
Section: Original Articlesmentioning
confidence: 99%
“…In patients with cirrhosis, malnutrition and increased circulating toxic substances may result in diffuse neuropathy [11,12] . Our subsequent study showed that N20-N65 IPLs of SEPs were helpful in the assessment of subclinical PSE (SPSE), and about a half of cirrhotic patients had SPSE [13] . The role of nutritional status in cirrhotic patients with SPSE remains uncertain.…”
Section: Introductionmentioning
confidence: 97%